Limbal stem cells carried by a four-dimensional -printed chitosan-based scaffold for corneal epithelium injury in diabetic rabbits - Wang, Mengyuan; Liu, Kaibin; Wang, Xiaomin; Shang, Zhen; Liu, Yiming; Pan, Nailong; Sun, Xueqing; Xu, Wenhua (Frontiers in Physiology, 2024)
Diabetic keratopathy induces corneal epithelial erosion and delayed epithelial regeneration. Patients with diabetes often undergo eye surgery because of several diabetes-associated complications, such as cataracts and glaucoma. Herein, we obtained and characterized deltaN p63-and adenosine triphosphate-binding cassette subfamily G member 2-expressing limbal stem cells (LSCs). Chitosan and carboxymethyl chitosan (CTH) were cross-linked to be an in situ thermosensitive hydrogel (ACH), which was printed through four-dimensional (4D) printing to obtain a porous carrier with uniform pore diameter (4D-CTH). Rabbits were injected with alloxan to induce diabetes mellitus (DM). Following this, the LSC-carrying hydrogel was spread on the surface of the cornea of the diabetic rabbits to cure corneal epithelium injury. Compared with the control group (LSCs only), rapid wound healing was observed in rabbits treated with LSC-carrying 4D-CTH. Furthermore, the test group also showed better corneal nerve repair ability. The results indicated the potential of LSCcarrying 4D-CTH in curing corneal epithelium injury. Altogether, 4D-CTH holds potential as a